2
$\begingroup$

The equation is $\ln{x}+\ln{(x-1)}=\ln{2}$ . I have worked it all the way through, and after factoring the $x^2-1x-2$ I got $x=2$, $x=-1$, but my question is: Can we have both solutions or couldn't we have the negatives?

$\endgroup$
1
$\begingroup$

Using the property of logaritm $\ln a+\ln b =\ln (a\cdot b)$ we obtain $$\ln x(x-1)=\ln 2 $$ Now, for the property $\ln u =\ln v \Rightarrow u=v$ the obtain that $$x(x-1)=2 \Rightarrow x^2-x-2=0 $$ Then, we obtain $x=2$ and $x=-1$, but $x=-1$ is not solution of the equation because $\ln (-1)\not \in \mathbb{R}$ (the function $f(x)=\ln x$ is defiined when $x>0$).

Conclusion: the equation $\ln x+\ln (x-1)=\ln 2$ have the solution $x=2$.

$\endgroup$
  • $\begingroup$ Hope this helps $\endgroup$ – ZHN Apr 9 '14 at 22:32
0
$\begingroup$

The easiest way is indeed to combine them: $$ \ln \left[x(x-1)/2\right] = 0 $$ implying that $x(x-1) = 2$ or $x^2 - x - 2 = 0$, which indeed has exactly two solutions at $x = 2$ and $x= -1$.

But $x=-1$ cannot be a solution, since the original equation is only defined for $x \ge 1$, so the only solution is $x=2$.

$\endgroup$
  • $\begingroup$ I think that the solution $x=-1$ deserves a comment. $\endgroup$ – ajotatxe Apr 9 '14 at 22:23
  • $\begingroup$ @ajotatxe I'm sorry, I revised a couple of times, not sure if your remark is still relevant? $\endgroup$ – gt6989b Apr 9 '14 at 22:24
0
$\begingroup$

$x=-1$ is, in some sense, a solution of the equation $\ln x+\ln (x-1)=\ln2$. The problem is that $\ln(-1)$ and $\ln(-2)$ are complex numbers. But in complex analysis, logarithms are multivaluated. Namely: $$\ln(-1)=(\pi+2k_1\pi)i$$ $$\ln(-2)=\ln2+(\pi+2k_2\pi)i$$

So $\ln(-1)+\ln(-2)=\ln 2+2(1+k_1+k_2)\pi i$. You can take certain branches of the logarithm to satisfy the equation, for example $k_1=-1$, $k_2=0$. But for other branches, it doesn't work.

Moreover, $x=-1$ is a solution of the equation $\ln(x^2-x)=\ln 2$. This equation is not the same as the other because the identity $\ln x+\ln(x-1)=\ln(x^2-x)$ only works for $x>0$. For $x<0$ we need those branches.

$\endgroup$
0
$\begingroup$

$$\ln(x)+\ln(x-1)=\ln(2)\\ \implies \ln({x}({x-1}))=\ln(2)\\ \implies {x}({x-1})=2\\ \implies x^2-x-2=0\\ \implies x=\dfrac{1\pm3}{2}=-1,2$$ However, only $x=2$ satisifies the equation.

$\endgroup$
  • $\begingroup$ @IlaIsabelle Sure! $\endgroup$ – user122283 Apr 9 '14 at 22:38
  • $\begingroup$ Ehm, $\ln x+\ln(x-1)=\ln(x(x-1))=\ln(x^2-x)$. You get $x=2$ just by chance. $\endgroup$ – egreg Apr 9 '14 at 22:54
  • $\begingroup$ @egreg Thanks. I edited my answer. $\endgroup$ – user122283 Apr 9 '14 at 22:57

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.